The entrepreneurial venture : readings selected - Stevenson, Howard H.; Roberts, Michael J.; Bhidé, Amar.; Sahlman, William A. (Harvard Business School Press, 1999)
This book is about: Strategies and tactics for starting, acquiring, and growing the vemture; Innovation and entrepreneurship in the larger company; Entrepreneurship in the nonprofit sector; ...